UNDERWRITING PADA ASURANSI JIWA SYARIAH DALAM PERSPEKTIF MAQASHID SYARIAH (STUDI KASUS PADA ASURANSI TAKAFUL KELUARGA CABANG BENGKULU) - Muhammad Ilham (IAIN Batusangkar, 2020)
The problems discussed in this paper are underwriting in sharia life insurance case studies on the Takaful insurance Bengkulu family branch. The aim is to find out the implementation of underwriting, factors that are considered underwriters, and how Maqasid sharia views on underwriting implementation at the Bengkulu Branch Family Takaful Insurance.The method used is descriptive qualitative analysis. In this case the writer describes the data the author gets from interviews and documentation from primary data sources and secondary data, while the data analysis techniques used are inductive analysis techniques by taking keywords from the results of interviews, then making narratives with easy-to-understand relationship patterns, then steps finally verify and draw conclusions from the results of the study.Based on the research that the author did in the Bengkulu Branch Family Takaful Insurance, it can be concluded that underwriting starts from field underwriting, verification of file and application data, collecting additional information, assessing risk, and underwriting decisions. Types of decisions, namely; insurance is accepted standard, insurance is accepted substandard, insurance is postponed, and insurance is refused. Then the factors that are considered by the underwriter in selecting risk include medical and non-medical factors. Maqasid sharia's view of underwriting is the first protection of the soul (Hifz al-Nafs). The legal objectives of underwriting are so that the risks are relatively homogeneous from certain groups of participants in order to provide a risk sharing scheme that is propo”rtional, fair and affordable to fellow policyholders against the risks that will be experienced. Second protection of property (Hifz al-Maal) The legal objective of underwriting is that the relatively large risks are offset by large savings and savings funds, in order to provide a risk sharing scheme that is proportional, fair and affordable to fellow policyholders and also provide space for companies to manage the premium funds on productive roads which are certainly in accordance with Islamic principles